COVID-19 Lockdown and Domestic Violence: Evidence from Internet-Search Behavior in 11 Countries - Berniell, Inés (2020)
We study the impact of the COVID-19 pandemic on domestic violence in 11 countries with different ex-ante incidence of domestic violence (DV) and lockdown intensity. We use a novel measure of DV incidents that allows us to make cross-country comparisons: a Google search intensity index of DV-related topics. Our difference-indifference estimates show an increase in DV search intensity after lockdown (31%), with larger effects as more people stayed at home (measured with Google Mobility Data). The peak of the increase in DV appears, on average, 7 weeks after the introduction of the lockdown. While we observe that the positive impacts on DV is a widespread phenomenon, the effect in developed countries is more than twice as strong as in Latin American countries. We show that the difference in impact correlates with the intensity of compliance with stay-at-home measures in the two groups.